Adaptation of Public Spaces to Climate Change Case Study of Lodz - BOCHENEK Anna; KLEMM Katarzyna; STEFAŃSKA Magdalena (Architecture, Civil Engineering, Environment)
Climate change is nowadays one of the most important problems that affects urban areas, where over half of the population lives. Due to the continuously growing population, significant number of citizens will be affected by its impact. For this reason, one of the steps to adapt cities to changing climate conditions is the implementation of adaptation strategies based on blue-green infrastructure elements.